UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DENGAN MENERAPKAN MODEL PEMBELAJARAN SNOWBALL TROWING PADA MATERI SEGITIGA DAN SEGIEMPAT - Pramono, Refo; Herawaty, Dewi; Fachruddin S., M. (JP2MS, 2017)
This study aims to improve the activity and student learning outcomes by applying the learning model Snowball Throwing. The type of research conducted is Classroom Action Research (PTK) with data collection techniques through student observation sheets and test results learning. The results showed that the application of Snowball Throwing learning model can improve the activity and learning outcomes of students of class VII SMPN 3 4 Bengkulu City. Improved student learning outcomes can be seen from the average learning outcomes from cycle I to cycle III. In cycle I The average of student learning achievement is 74,57. In the second cycle average student learning outcomes are 75.14. In the third cycle the average of student learning outcomes is 78.14. Then the application of Learning Model Throwing Snowball can improve student learning outcomes as seen from an average increase of cycle I to cycle III, ie 74.57; 75,14; 78.14. Keywords: Model Snowball Throwing, learning activities and learning outcomes.